The mediating role of sleep quality in the relationship between dispositional mindfulness and fatigue in Chinese nurses during the COVID-19 pandemic - Caijun Dai; Pinglang Hu; Feifan Yan; Xuejiao He; Weizhen Cheng; Lihua Yu; Achang Fang; Xiaoling Meng; Meiyang Lou; Youying Chen; Danli Chi; Huasu Zhou; et al. (BMC, 2023)
Abstract Background During the COVID-19 epidemic in China, clinical nurses are at an elevated risk of suffering fatigue. This research sought to investigate the correlation between dispositional mindfulness and fatigue among nurses, as well as the potential mediation role of sleep quality in this relationship. Methods This online cross-sectional survey was performed from August to September 2022 to collect data from 2143 Chinese nurses after the re-emergence of COVID-19. The significance of the mediation effect was determined through a bootstrap approach with SPSS PROCESS macro. Results Higher levels of dispositional mindfulness were significantly negatively related to fatigue (r = -0.518, P < 0.001) and sleep disturbance (r = -0.344, P < 0.001). Besides, insufficient sleep was associated with fatigue (r = 0.547, P < 0.001). Analyses of mediation revealed that sleep quality mediated the correlation of dispositional mindfulness to fatigue (β = -0.137, 95% Confidence Interval = [-0.156, -0.120]). Conclusions In the post-COVID-19 pandemic era, Chinese nurses' dispositional awareness was related to the reduction of fatigue, which was mediated by sleep quality. Intervention strategies and measures should be adapted to improve dispositional mindfulness and sleep quality to reduce fatigue in nurses during the pandemic.